Review of optimal resource allocation scheme for 5G Internet of vehicles - Chengyu ZHENG; Yiting YAO; Hongbin LIANG; Lei WANG (Dianxin kexue)
As a necessary part of the development of intelligent transportation, the Internet of vehicles (IoV) accelerates the construction of intelligent transportation infrastructure in China, which plays an important practical significance to the construction of smart city.The number of vehicles and the massive data generated by them make the transmission conflict rate between communication vehicle nodes rise significantly, and communication resources and computing resources are in short supply.Therefore, the effective resource allocation scheme can ensure the communication quality of vehicle networking, thereby improving the reliability of vehicle communication and reducing the time delay.Firstly, the influence of IoV on the development status of intelligent transportation at home and abroad and the bottlenecks of the development of IoV were analyzed.Secondly, in terms of the efficiency and safety of smart transportation, the resource allocation problem of IoV was analyzed.Thirdly, by summarizing the advantages of 5G technology, the contribution of 5G in the optimization allocation and management of vehicle networking resources was analyzed.Finally, combined with the application of artificial intelligence technology in the context of Internet of vehicles communication, computing and storage resource optimization allocation and management, the development prospect of intelligent transportation based on 5G+V2X was proposed.